Digital Flashcards to Boost Children's Interest in English Communication - Nasution, Kholilah Yuniar; Sitepu, Reysa Putri Br.; Manurung, Rani Angelika; Lismawarni; Pulungan, Rizqi Himmawan Ardya; Panggabean, Vandri Perdana (Universitas Kapuas, 2024)
This study examines the effectiveness of combining digital flashcards with the Communicative Language Teaching (CLT) approach to enhance interest and communication skills in English among elementary school children. Conducted at SD Negeri 058116 Kwala Sawit in Tangkahan, a rural tourist area in North Sumatra, the research employed a Classroom Action Research (CAR) model to test the impact of this innovative method in an under-resourced educational setting. The study involved 56 grades 5 and 6 students who completed two planning cycles: implementation, observation, and reflection. Results indicated a substantial increase in students' interest and engagement, with a 10.25% improvement in learning interest. Moreover, student proficiency in conversational English rose, as 72% of fifth graders and 78% of sixth graders demonstrated correct responses in practical dialogues after the intervention, a rise from the initial 40%. This study offers insights into the potential of digital, interactive tools to support language acquisition, especially in rural or resource-limited environments. These findings suggest that digital flashcards, combined with CLT, can provide a sustainable and engaging approach to language learning, fostering enthusiasm and communicative competence in young learners.